Implementation of Education Character to Overcome Students’ Harvestion - A. Aco Agus; Nur Qalbi; Khaer Hanafie; Muhammadong Muhammadong (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2020)
Harassment among students are worrying phenomenon in the current digital era. Becausing the news spreads fast but does not create a deterrent effect for students especially at the junior high school level. This study aims to determine the forms of harassment that are common in the school environment, sanctions imposed on perpetrators and finally efforts to overcome harassment by the school. To achieve these objectives the researchers used a descriptive qualitative approach to change, explain the phenomenon of abuse that occurs among students in schools. Types of descriptive research are primary data sources namely informants consisting of school principals, teachers, and students. And the Secondary data is documents. Data collection techniques used were observation, interviews, and documentation. The data analysis technique used is descriptive qualitative. The results showed that there were many forms of violence which were commonly found by students in the school environment, both physical and psychological violence. Physical form includes, a) hitting, b) pinching, c) pressing down on the ear, and d) throwing using shoes. The form of psychological violence is giving harsh words. sanctions given by teachers for violence against students, namely: a) verbal reprimands, and b) written reprimands. The efforts made by teachers to overcome violence against students are: a) preventive measures (holding dialogue between teachers, parents, and students b) repressive actions by calling on school to avoid harassing student.